Is the relationship between inward FDI and spillover effects linear? An empirical examination of the case of China - Buckley, Peter J; Clegg, Jeremy; Wang, Chengqi (Journal of International Business Studies, 2007)
This paper finds that the nationality of ownership of foreign investors significantly impacts upon productivity spillover effects, revealing a curvilinear relationship with foreign direct investment on data for overseas Chinese (Hong Kong, Macau and Taiwan) multinational enterprises, but not for other (Western) firms. This relationship is most pronounced for low-technology host industries. These findings suggest that the curvilinear form is more appropriate to the future study of the spillover effects of foreign presence.